CLASSIFICATION OF INTRAVASCULAR ULTRASOUND IMAGES BASED ON NON-NEGATIVE MATRIX FACTORIZATION FEATURES AND MAXIMUM LIKELIHOOD CLASSIFIER - Rajan A (International Journal of Advances in Signal and Image Sciences, 2018)
The amount of plaque in coronary arteries in any particular point is identified by the IntraVascular UltraSound (IVUS) images. The classification of IVUS images is very important to diagnose various coronary artery diseases. In this study, the classification of IVUS images based on Non-negative Matrix Factorization (NMF) technique and Maximum Likelihood Classifier (MLC) is presented. Initially, the IVUS images are given to frost filter to remove speckle noise as the imaging technique uses ultrasound waves. Then, NMF technique is employed to extract the features and stored in database. Then MLC is used for classification of IVUS images for both normal and abnormal categories. The IVUS Image Classification (IIC) system obtains 98% classification accuracy by using NMF features and MLC classification.